Needs Analysis for Developing STEM-PjBL-SSI-Based e-LKPD on Renewable Energy Using Oil Palm Empty Fruit Bunch Waste Context - Ratna Yuningsih; Kartini Herlina; Undang Rosidin; M Setyorini (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
Renewable energy learning in science education requires contextual teaching materials that connect scientific concepts with local environmental issues and future-oriented skills. However, current classroom practices still face limitations in integrating project-based learning, socio-scientific issues, and entrepreneurial-oriented activities into structured learning resources. This study aimed to analyze the needs for developing a STEM-PjBL-SSI-based electronic student worksheet (e-LKPD) on renewable energy using oil palm empty fruit bunch waste as a local biomass context. A descriptive quantitative approach was employed through a survey involving 29 science teacher respondents. The data were collected using a questionnaire and analyzed descriptively using percentages. The results showed that Problem-Based Learning was the most frequently used learning model, applied by 51.7% of respondents, followed by Project-Based Learning at 37.9%, Discovery Learning at 27.6%, and Inquiry-Based Learning at 10.3%. The most commonly used teaching methods were discussion at 62.1% and experiment at 58.6%, while lectures were still used by 34.5% of respondents. In terms of learning resources, teachers mostly used learning videos at 72.4%, the internet at 65.5%, reference books at 55.2%, modules at 48.3%, and student worksheets at 44.8%. The findings also revealed that 62.1% of teachers were familiar with Socio-Scientific Issues, while misconceptions regarding renewable energy sources were still found among some respondents. Although 75.9% of teachers developed their own student worksheets, the existing worksheets had not systematically integrated STEM, project-based activities, socio-scientific issues, and entrepreneurial skill development. Therefore, the development of STEM-PjBL-SSI-based e-LKPD using oil palm empty fruit bunch waste as a renewable energy context is needed to support more contextual, interactive, and skill-oriented science learning.